Technology and understanding of post-fracturing coring in three-dimensional development zone of Fuling shale gas, Sichuan Basin, SW China - Huanquan SUN; Zhiyong LU; Li LIU; Jichao FANG; Aiwei ZHENG; Jiqing LI; Yuqiang ZHANG; Jialin XIAO (Petroleum Exploration and Development)
The core sampling experiments conducted after hydraulic fracturing were carried out in the three-dimensional development zone of Fuling shale gas. Six coring wells of different well types were systematically designed. Based on the integrated engineering technology of post-fracturing drilling, coring and monitoring of shale and the analysis of fracture source tracing, the evaluation of the fracture network after fracturing in the three-dimensional development of shale gas was conducted. The data of core fractures after fracturing indicate that three major types of fractures are formed after fracturing: natural fractures, hydraulic fractures, and fractures induced by external mechanical force, which are further classified into six subcategories: natural structural fractures, natural bedding fractures, hydraulic fractures, hydraulically activated fractures, drilling induced fractures, and fractures induced by core transportation. The forms of the artificial fracture network after fracturing are complex. Hydraulic fractures and hydraulically activated fractures interweave with each other, presenting eight forms of artificial fracture networks, among which the “一”-shaped fracture is the most common, accounting for approximately 70% of the total fractures. When the distance to the fractured wellbore is less than 35 m, the density of the artificial fracture network is relatively high; when it is 35–100 m, the density is lower; and when it is beyond 100 m, the density gradually increases. The results of the fracture tracing in the core sampling area confirm that the current fracturing technology can essentially achieve the differential transformation of the reservoir in the main area of Jiaoshiba block in Fuling. The three-layer three-dimensional development model can efficiently utilize shale gas reserves, although there is still room for improvement in the complexity and propagation uniformity of fractures. It is necessary to further optimize technologies such as close-cutting combined with temporary blocking and deflection within fractures or at fracture mouths, as well as limited flow perforation techniques, to promote the balanced initiation and extension of fractures.